THE EXTENSION KNOWLEDGE NEEDS OF FARMERS DATE PALM POLLINATION AT BALDROUZ DISTRICT DIYALA PROVICE - AL-Aljeeli, Sahab Ayed; Ali, Majid K.; Jasim, Mahmood H. (Diyala Agricultural Sciences Journal, 2011)
The aim of the research was to determine the extension knowledge needs of farmers Date palm at Baldrouz District , and to determine the domains integration and to diagnosis the most important problems confronting the farmers in the pollination process . Baldrouz District was chosen to do the research. Random sample of (40) framer of Data palm was selected . The questionnaire was used to collect date using personal interview . The results revealed that the level of extension knowledge needs of date palm pollination was medium. Appositive significant correlation between the extension knowledge needs and each of the variable studied included getting study, the importance of the crop in the yearly farmer agricultural income and the date palm cultivated area . It have been found the highest extension knowledge needs in pollination process show up in the domain of the effective factors at pollination process . The most important problem facing the farmers were depend on personal knowledge for doing the date palm pollination process . The research recommends the interest of the date palm and its productions with provide the date palm farmers with applied agriculture information about date palm pollination , that’s the important process of the date palm services .It is also recommended that is necessary for monitoring apply the scientific recommendation as a complete bundle especially recommendations of date palm pollination.